2002
DOI: 10.1111/j.1745-9125.2002.tb00949.x
|View full text |Cite
|
Sign up to set email alerts
|

Strain, Personality Traits, and Delinquency: Extending General Strain Theory

Abstract: Although Agnew's (1992) general strain theory (GST) has secured a fair degree of support since its introduction, researchers have had trouble explaining why some individuals are more likely than others to react to strain with delinquency. This study uses data from the National Survey of Children to address this issue. Drawing on Agnew (1997) and the psychological research on personality traits, it is predicted that juveniles high in negative emotionality and low in constraint will be more likely to react to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
446
5
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(485 citation statements)
references
References 76 publications
24
446
5
6
Order By: Relevance
“…Many of the main concepts pertaining to GST have been thoroughly tested, most specifically, the direct relationship between strain and delinquency. Overall, the research has consistently found a positive relationship between strain and delinquent behavior (e.g., Agnew, 2002;Agnew et al, 2002;Agnew & White, 1992;Aseltine et al, 2000;Brezina, Piquero, & Mazerolle, 2001;Hay, 2003;Paternoster & Mazerolle, 1994). Indeed, in almost every published test of GST, at least one measure of strain has been found to positively influence delinquency.…”
Section: Empirical Research On Gstmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the main concepts pertaining to GST have been thoroughly tested, most specifically, the direct relationship between strain and delinquency. Overall, the research has consistently found a positive relationship between strain and delinquent behavior (e.g., Agnew, 2002;Agnew et al, 2002;Agnew & White, 1992;Aseltine et al, 2000;Brezina, Piquero, & Mazerolle, 2001;Hay, 2003;Paternoster & Mazerolle, 1994). Indeed, in almost every published test of GST, at least one measure of strain has been found to positively influence delinquency.…”
Section: Empirical Research On Gstmentioning
confidence: 99%
“…Another limitation involves the exclusion of variables hypothesized to condition the effects of strain on delinquency including delinquent peer associations, situational and dispositional anger (e.g., Capowich et al, 2001), negative emotionality/low constraint (e.g., Agnew et al, 2002), social bonding (e.g., Mazerolle, 1998), and exposure to delinquent peers (e.g., Paternoster & Mazerolle, 1994). Again, the data did not permit such inclusion.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research regarding human personality is extensive (see Moffitt, Avshalom, Rutter, and Silva, 2001;Agnew et al, 2002), and an exhaustive examination would be inappropriate here. Some human traits have repeatedly shown up in delinquency research, however, and serve as contingencies to examining deterrent effects.…”
Section: Type Of Individualmentioning
confidence: 99%
“…However there is evidence that Self-Control (associated with Conscientiousness), Emotional Stability, and Agreeableness are important protective factors against criminal activity (John et al1994, Agnew et al 2002. Controlling for the influence of education and cognitive ability, these traits appear equally predictive of lower criminal activity (Heckman, Stixrud, and Urzua, 2006).…”
mentioning
confidence: 99%